Triacylglycerols profiling in plant oils important in food industry, dietetics and cosmetics using high-performance liquid chromatography-atmospheric pressure chemical ionization mass spectrometry - Lísa, Miroslav; Holcapek, Michal (Journal of chromatography. A, 2008)
Optimized non-aqueous reversed-phase high-performance liquid chromatography method using acetonitrile-2-propanol gradient elution and the column coupling in the total length of 45 cm has been applied for the high resolution separation of plant oils important in food industry, dietetics and cosmetics. Positive-ion atmospheric pressure chemical ionization mass spectrometry is used for the unambiguous identification and also the reliable quantitation with the response factors approach. Based on the precise determination of individual triacyglycerol concentrations, the calculation of average parameters important in the nutrition is performed, i.e. average carbon number, average double bond number, relative concentrations of essential, saturated, monounsaturated and polyunsaturated fatty acids. Results are reported in the form of both chromatographic fingerprints and tables containing relative concentrations for all triacylglycerols and fatty acids in individual samples. In total, 264 triacylglycerols consisting of 28 fatty acids with the alkyl chain length from 6 to 26 carbon atoms and 0 to 4 double bonds have been identified in 26 industrial important plant oils.
Keywords: reprodukovatelnost výsledků; Cosmetics; Chromatography, High Pressure Liquid; kosmetické přípravky; atmosférický tlak; Triglycerides; Atmospheric Pressure; Plant Oils; triglyceridy; Food Industry; Dietetics; Reproducibility of Results; hmotnostní spektrometrie; dietetika; vysokoúčinná kapalinová chromatografie; potravinářský průmysl; oleje rostlin; Mass Spectrometry